2015
DOI: 10.4102/aveh.v74i1.307
|View full text |Cite
|
Sign up to set email alerts
|

Is the central corneal thickness of diabetic patients thicker than that of non-diabetics’ eyes?

Abstract: The purpose of the study was to evaluate central corneal thickness in diabetic patients and to compare the results with controls without diabetes mellitus. Sixty-five diabetic patients (65 eyes) constituted the study group, and 50 eyes were from the healthy control group (50 non-diabetic patients). The study group was subdivided into group 1 (no diabetic retinopathy, n = 35), group 2 (mild to moderate nonproliferative diabetic retinopathy, n = 20), and group 3 (proliferative diabetic retinopathy, n = 10). Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…Our results were concordant with those by other researchers globally, who either showed increased or significantly increased mean CCT in NPDR and PDR compared to control and NDR. 9,12,[14][15][16][17][18][19] Mean CECC observed by us was similar in control and patients with NDR. Significant reduction in CECC compared to control and NDR was also observed in NPDR and PDR.…”
Section: Discussionmentioning
confidence: 52%
“…Our results were concordant with those by other researchers globally, who either showed increased or significantly increased mean CCT in NPDR and PDR compared to control and NDR. 9,12,[14][15][16][17][18][19] Mean CECC observed by us was similar in control and patients with NDR. Significant reduction in CECC compared to control and NDR was also observed in NPDR and PDR.…”
Section: Discussionmentioning
confidence: 52%
“…The present study showed that the presence of DR affect CCT measurement. Mathebula and Segoati found no statistically significant difference between CCT in patients with DR and those without DR [25]. Unlike, another study by Parekah et al which reported a thicker CCT in patients with DR compared to controls [13].…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies measured CCT in type I and type II diabetes mellitus (with and without DR) without comparing the values between the two groups [22][23][24][25]. While other studies measured the CCT in one type of diabetes mellitus only [13,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…This review is limited to studies conducted on normal healthy African samples and excludes those that have included individuals with systemic conditions 75 (diabetes mellitus and http://www.avehjournal.org Open Access hypertension) and glaucoma disorders 76,77 , as these factors can influence CCT measurements. 1,48,64,78 In conclusion, this review draws attention to the assumption that CCT measurements in one African population cannot necessarily be extrapolated to other African populations. This implies that there may be other factors, even within the same race group, that contribute to differences in CCT measurements.…”
Section: Discussionmentioning
confidence: 99%